3 n ( 4 n 2 + 6 n + 3 )
Let n be a positive integer which makes the above product a triangular number .
How many solutions are there for n ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There isn't a need to use the substitution of p=2n+1. You just need to set "n' as the subject to (n/3)(4n^2+6n+3) = m(m+1)/2, which is n = (1/2)( (3m^2 + 3m +1)^(1/3) - 1).
Or equivalently, (2n+1)^3 = 3m^3 +3m +1 <=> (2n+1)^3 + m^3 = (m+1)^3 <==> Absurd by FLT.
A triangular number has the form 2 n ( n + 1 ) , hence we require:
2 n ( n + 1 ) = 3 4 n 3 + 6 n 2 + 3 n ⇒ 3 n 2 + 3 n = 8 n 3 + 1 2 n 2 + 6 n ⇒ 0 = 8 n 3 + 9 n 2 + 3 n
or 0 = n ( 8 n 2 + 9 n + 3 ) (i)
The quadratic term is irreducible and has roots n = 1 6 − 9 ± 8 1 − 4 ( 8 ) ( 3 ) = 1 6 − 9 ± 1 5 i , as well as n = 0 is the third remaining root in (i) . There are NO values n ∈ N that satisfy the triangular number condition.
Problem Loading...
Note Loading...
Set Loading...
Let p = 2 n + 1 . Then 3 n ( 4 n 2 + 6 n + 3 ) = 6 2 n ( 4 n 2 + 4 n + 1 + ( 2 n + 1 ) + 1 ) = 6 p − 1 ( p 2 + p + 1 ) = 6 p 3 − 1 .
Then for a triangular number equality, let 6 p 3 − 1 = 2 m ( m + 1 ) for some m .
Then p 3 − 1 = 3 m 2 + 3 m .
p 3 + m 3 = m 3 + 3 m 2 + 3 m + 1 = ( m + 1 ) 3 .
However, according to Fermat's last theorem , no integer solutions for the equation in a form of x n + y n = z n .
Therefore, there are no integer solutions n that can satisfy all constraints.